Choice of low-pass filter influences practical interpretation of ball kicking motions: the effect of a time-frequency filter method - Augustus, S.; Amca, A. M.; Hudson, P. E.; Smith, N. (Sports Biomechanics, 2023)
When studying ball kicking, conventional low-pass filters may distort kick leg kinematics near the time of foot-to-ball contact, leading to flawed practical interpretation of the skill. Time-frequency filters are a viable alternative but are not widely used. This study compared a fractional Fourier filter (FrFF) with conventional filters (CF) methods for estimating common parameters used to define kicking performance. Instep kicks from 23 experienced soccer players were captured by 3D motion analysis (1000 Hz), and kick leg foot velocities, knee angular velocities and ankle dorsi-plantarflexion angles compared between the FrFF and variations of a Butterworth CF. The FrFF and CFs using a higher cut-off frequency (>70 Hz) successfully detected lower leg motion prior to, during and following impact, whereas CFs with low cut-off frequencies (<20 Hz) attenuated motion near impact. Truncating data at impact provided valid pre-impact kinematics, but ignored information thereafter. Rather than decelerating the lower leg to conserve accuracy, "kicking through the ball" should be considered a valid coaching cue. Further, controlling ankle plantar flexion to ensure efficient impact mechanics may be important for skilled kicking. Practitioners should consider how choice of filter will affect their data, and use of time-frequency methods can help inform empirically grounded coaching practices.